1969
DOI: 10.1113/jphysiol.1969.sp008773
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of lung capillaries to macromolecules in foetal and new‐born lambs and sheep

Abstract: SUMMARY1. The permeability of lung capillaries to macromolecules was investigated in immature and mature foetal lambs, new-born lambs and young sheep. The placental circulation of the foetal animals was maintained intact after delivery by Caesarian section. New-born lambs and sheep were mechanically ventilated. Samples of plasma and lymph that had drained from the lung via the thoracic duct were collected over a period of 1-5 hr.2. The proteins in plasma and lymph samples were separated by fractionation on col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…The role of lung lymphatics in protecting against pulmonary edema has been suggested (19,20,30), but not generally appreciated (31). Our studies show that lung lymphatics in awake sheep have the capacity to clear large quantities of filtered fluid (up to 85 ml/h in animal S36-72) and protein.…”
Section: Response To Pseudomonas Infusionmentioning
confidence: 57%
See 1 more Smart Citation
“…The role of lung lymphatics in protecting against pulmonary edema has been suggested (19,20,30), but not generally appreciated (31). Our studies show that lung lymphatics in awake sheep have the capacity to clear large quantities of filtered fluid (up to 85 ml/h in animal S36-72) and protein.…”
Section: Response To Pseudomonas Infusionmentioning
confidence: 57%
“…The ratios of extravascular lung water to dry weight of bloodless lung (Qwl/dQl) are listed in Table IV (18,19).…”
Section: Response To Pseudomonas Infusionmentioning
confidence: 99%
“…To achieve these differences in the presence of the aforementioned pore radii, Boyd et Finally, we must explain why other investigators have found a three-to fourfold difference in lymph flow between lambs and sheep in acute experiments (2)(3)(4), compared with the 57% difference we are reporting. Although there was an eightfold difference in body weight between lambs and sheep, the lung tissue of the lambs was only one-fourth the mass of lung tissue of the sheep.…”
mentioning
confidence: 70%
“…Boyd et al (4) reported that the concentration of both albumin and globulin in lymph relative to plasma was greater in newborn than in older sheep. They did not measure pulmonary vascular pressures.…”
mentioning
confidence: 99%
See 1 more Smart Citation